Step-by-step strategy of electron utilization by binary cocatalysts: Coupling electron-reservoir MoS2 with proton-reduction cobaloxime for enhanced photocatalytic hydrogen evolution - Jianguo He; Lin Chen; Jiahui Yang; Qiongqiong Wang; Hongli Zhang; Keying Lin; Wei Wang; Dong Feng; Baojun Ma (Fuel, 2026)

Analysis of the deterioration rule and perception mechanism of egg yolk powder odor based on volatile omics, molecular docking and molecular dynamics simulation - Jiahui Song; Enhui Ma; Renrui Zheng; Zhuohang Huang; Jun Jiang; Zhijie Bao; Songyi Lin (Food Research International, 2026)

Food-derived extracellular vesicles modulate ferroptosis: Implications for functional food development and healthy aging - Lin Zhang; Wangying Qiu; Mingrun Lu; Shuting Lan; Zuokai Lv; Haiyan Zhang; Yue Pang; Xingcan Zhang; Wenjing Xu; Haitao Wang; Jiahui Liu; Jiahui Ma; et al. (Food Research International, 2026)

Structural characterization of novel polysaccharides from Sargassum fusiforme with dual anticoagulant activity targeting thrombin and antithrombin III - Yue Zhu; Yuanlin Luo; Yunqin Shi; Jiahui Shao; Shunhao Lin; Xiuting Zhang; Yu Tang; Xiangwei Zhao; Jianping Jiang; Zhenzhong Yang (Food Chemistry, 2026)

A dynamic DNA nanoconstruct-integrated hydrogel: Reprogramming osteoimmune for diabetic bone defect repair - Mei Zhang; Xiao Fu; Zhen Zhao; Yiliu Zhou; Jiahui Xiong; Bo Huang; Yao He; Zhiqiang Liu; Yunfeng Lin (Chemical Engineering Journal, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Electronic configuration regulation and photocatalytic nitrogen fixation performance of the fourth-period d7/d8 metal catalysts - Xiaolu Xu; Jingyi Qu; Yangben Chen; Jiahui Lin; Yibo Zhang; Zhan Hu; Hui Zheng (Journal of Environmental Chemical Engineering, 2026)

Regulation of rice bran physicochemical properties, bioactive components and functional properties by synergistic fermentation of Bacillus subtilis and Aspergillus niger - Wenqing Zhao; Jiahui Zhou; Qian Lin; Xiangrui Ren; Li Niu; Wenhao Li (Food Bioscience, 2026)

Integrated thermal insulation and sound absorption in hierarchically architected 3D-printed dual-nanofiber aerogels - Yichao Yu; Yinxiao Jia; Xiaoxiao Lin; Mingkun Zhang; Sisi Wang; Weiling Zhu; Shaohua Jiang; Jiahui Shen; Jiajia Zheng; Zhonglue Hu; Yiming Chen (Chemical Engineering Journal, 2026)

Pd single atoms anchored on mesoporous C3N5: An exceptional photocatalyst for hydrogen production - Yang Wang; Cun-Feng Fan; Jiao-Yan Li; Xiao-Qin Zheng; Xuan-Yi Liu; Ying Zhou; Jiahui Kou; Hengming Huang; Lin-Bing Sun (Chemical Engineering Journal, 2026)

The cortical morphology of cingulate cortex and microarchitecture of cingulum bundle correlate with cancer pain and anxiety in lung cancer patients - Lin Tang; Xiaosong Lan; Xiaoyu Zhou; Yu Tang; Jiahui Zheng; Junhao Huang; Yong Tan; Jing Zhang; Hong Yu; Meng Lin; Hua Lan; Xinying Ren; et al. (Brain Imaging and Behavior, 2026)

Electron-deficient boron-doped bimetallic (ZnFe) catalyst for high-efficiency photocatalytic nitrogen fixation - Xiaolu Xu; Jiahui Lin; Yangben Chen; Yibo Zhang; Zhan Hu; Jingyi Qu; Zhexiao Zhu; Hui Zheng (Journal of Environmental Chemical Engineering, 2026)

The Use of Double-tube Multiplex TaqMan Real-time RT-PCR for the Simultaneous Detection of Foodborne Viruses in Shellfish - Peng Lin; Ling Chen; Qiang Wan; Zhihe Cai; Liang Xue; Qinghua Ye; Fufeng Jiang; Xiaoying Qu; Jiahui Huang; Huishu Huang; Yu Ding; Moutong Chen; et al. (Food Control, 2026)

Correction: Phylogenetic analysis, genetic diversity, and epidemiology of pigeon paramyxovirus type 1 in China - Chuqi Huang; Shaoyu Tu; Wei Sheng; Zhihao Wang; Zhipeng Lin; Jing Qian; Jiahui Zou; Hongbo Zhou (Archives of Virology, 2026)

ZBP1-driven PANoptosis in granulosa cells mediates follicular arrest in PCOS: integrated transcriptomic evidence and baicalin’s therapeutic potential - Jiahui Ye; Xiaoxia Zhao; Siyuan Cen; Bixia Zhang; Hengzhen He; Chao Song; Pinglan Ma; Hanmei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Knowledge-driven multimodal feature selection fusion and collaborative learning for underwater object tracking - Ning Li; Huimin Deng; Yuanzhi Zhang; Lin Huang; Jiahui Yin; Chunhua Zhu; Xuan Fei; Binglin Wu (Ocean Engineering, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

Sulfur-autotrophic treatment of Sb(V)-contaminated water across concentration levels: Toward effective antimony pollution control - Yahui Shi; Zhixiang Zhang; Heyu Wan; Lin Ma; Heng Chen; Ying Li; Jiahui Dai; Dongjin Wan (Process Safety and Environmental Protection, 2026)

Dietary myricetin inhibits AGEs formation during thermal processing in different pattern diets and alleviates AGEs-induced intestinal epithelial damage in Caco-2 cells - Luyan Liu; Kaiyue Sun; Xin Xie; Yanghui Chen; Jiahui Wang; Yaxin He; Junjie Yu; Meng Huang; Yan Lin; Juan Chen; Jian Liu; Xian Zhang (Food Chemistry, 2026)

Influence of Distance Metrics Under Different Temporal Units on Flood Season Staging with the Fisher Optimal Segmentation Method - Jiahui Lin; Jun Li (Water Resources Management, 2026)

Engineering synthetic microbial communities in the crop rhizosphere to advance agricultural systems - Jiayuan Wang; Ruixi Lin; Jiahui Gong; Kun Han; Bingyin Peng; Kai Liu; Binghai Du; Chengqiang Wang (Applied Soil Ecology, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

Computation-driven discovery of a next-generation canine monoclonal antibody for canine parvovirus therapy - Ying Li; Xiaoyu Zhang; Zhihao Wang; Mingqin Lin; Sheng Wang; Chengguang Zhang; Ling Zhao; Jiahui Zou; Hongbo Zhou (Veterinary Microbiology, 2026)

Quality formation in corn kernels during postharvest ripening: the influence of storage conditions on phenolic components and antioxidant activity - Fuyin Zhao; Haohai Li; Rixin Zang; Jiahui Pan; Jinying Zhu; Lin Xiu; Huimin Liu; Mingzhu Zheng; Meihong Liu; Jingsheng Liu (Food Chemistry, 2026)

Effects of low-level lead exposure on hematological parameters and the possible underlying mechanisms - Xiaojing Liao; Tao Lin; Zhaorui Zhang; Peng He; Haimei Wu; Xinyi Ouyang; Qianxi Li; Zihan Yu; Ziyan Zhang; Jiahui Wu; Yingxin Guo; Shanshan Wang; et al. (Environmental Pollution, 2026)

A novel double-layer composite material with excellent radiative cooling and thermal management for electronic devices - Haoxin Lv; Haixuan Liu; Jiahui Lin; Jintao Huang; Hanlin Xie; Xiaofeng Li; Yonggang Min; Xiang Lu (Chemical Engineering Journal, 2026)

Sesn2 is Associated with Attenuated Muscle Atrophy and Altered Expression of Key Myogenic and Autophagy Markers in Mdx Mice - Zubiao Song; Qing Lin; Jiahui Liang; Juanjuan He; Weixi Zhang (Journal of Molecular Neuroscience, 2026)

Metabolomics reveals GABA as a key mediator of salinity stress in razor clam - Geqi Gao; Zihan Lin; Yuting Han; Mengwei Shang; Jiahui Sun; Donghong Niu; Jiale Li (Aquaculture, 2026)

Identification and algicidal mechanism of extracellular polysaccharides from Sulfitobacter pseudonitzschiae H46: A novel biocontrol agent for Chattonella marina bloom - Jiaxuan He; Lin Yang; Xin Yin; Jiahui Zhao; Yadan Deng; Jinfeng Ding; Shuai Wang; Bin Han; Li Zheng (Harmful Algae, 2026)

Exploring the impact of dietary extracellular vesicles on gut health: homeostasis, barrier defense, immunity, and signaling pathways - Haiyan Zhang; Jianing Tu; Yue Pang; Jiahui Ma; Lin Zhang; Chenyu Xue; Yuhao Liu; Weichen Hong; Mizhou Hui; Bailiang Li; Na Dong; Chenzhe Gao (Food Research International, 2026)

Reforming trade governance for sustainable resource flows: Ecologically unequal exchange in Pan-Eurasia - Jiahui Li; Lin Huang; Jun Zhai; Shihao Wang (Environmental Impact Assessment Review, 2026)

Amplifying self-protective room-temperature phosphorescence in carbon dots via electronic-state engineering - Jiahui Tan; Lin Cui; Jian Lei; Jiayi Chen; Yurong Wei; Zhigang Ren; Jie Wang (Chemical Engineering Journal, 2026)

Metabolic engineering of dammarane-type ginsenoside biosynthesis in rice endosperm and evaluation the anticancer efficacy of ginsenoside-biofortified rice in vitro and in vivo - Kai You; Cuiyuan Jing; Jiahui Wen; Lin Tang; Bowen Huang; Dongdong Zeng (Chemical Engineering Journal, 2026)

CBC3T-3: a novel patient-derived cisplatin-resistant distal cholangiocarcinoma cell line harboring multiple TP53 missense mutations - Jiahui Xi; Mingzhen Bai; Ruyang Zhong; Chongfei Huang; Ruoshui An; Long Gao; Haidong Ma; Liang Tian; Jinyu Zhao; Ningzu Jiang; Xiang He; Leiqing Wang; et al. (Human Cell, 2026)
Distal cholangiocarcinoma (dCCA) is a malignant tumor characterized by a challenging diagnosis, high invasiveness, and extremely poor prognosis. Research on dCCA is limited by the scarcity of reliable patient-derived preclinical tumor models. This study established a novel human distal cholangiocarcinoma cell line, CBC3T-3, and systematically characterized its biological properties, genomic features, and potential for clinical application. This cell line was extracted from postoperative distal cholangiocarcinoma tumor from a 54-year-old male patient. It was stably passaged (> 50 generations) through primary culture and condition optimization, preserving the same pathology as that of the primary tumor. Whole-exome sequencing (WES) confirmed somatic mutations, tumor mutation burden, single-sample clonal structure, driver genes, and drug resistance genes in CBC3T-3 cells, revealing their genomic characteristics. Functional assays demonstrated that CBC3T-3 cells exhibit strong capabilities for proliferation, migration, and invasion in vitro. In a subcutaneous xenograft model in immunodeficient mice, palpable tumor nodules developed within 4 weeks, reflecting the clinical characteristics of rapidly progressive disease. Drug sensitivity analysis revealed that, compared with TFK-1 cells, CBC3T-3 cells presented significantly greater responses to paclitaxel, gemcitabine, and oxaliplatin but relatively poor responses to 5-FU and cisplatin. The integration of drug resistance gene findings from WES suggests that TP53 missense mutations may mediate primary resistance to cisplatin. The establishment of the CBC3T-3 cell line enhances the research toolkit for dCCA. Its genomic characteristics and functional plasticity provide a reliable preclinical tumor model for developing precision therapies and investigating drug resistance mechanisms.

A novel bZIP transcription factor VvbZIP026 induces anthocyanin biosynthesis and acylation modification in response to abscisic acid in ‘Summer Black’ grape - Zouchumo Ge; Mengwen Yao; Ting Chen; Yao Yao; Jiahui Lin; Jingtian Huo; Guiren Qi; Zhaosen Xie; Xianan Zhang; Lei Wang; Feng Leng (Plant Science, 2026)

A bio-based composite phase-change material composed of pineapple peel and polyethylene glycol for efficient thermal energy storage - Haixuan Liu; Haoxin Lv; Yongshuang Xiao; Jiahui Lin; Yonggang Min; Jintao Huang (Biomass and Bioenergy, 2026)

Unraveling the impacts of blue-green-gray landscape patterns on PM2.5 in high-density urban areas: A case study of Xi’an - Baojun Yang; Lin Zhang; Danchen Yang; HuiYing Ma; Haifan Xie; Jiahui Hou; Ling Qiu; Tian Gao (Atmospheric Pollution Research, 2026)

Adjuvant-metal-ion-chelating PTEN mRNA with cell-membrane-coating augments the immune sensitivity for precise cancer immunotherapy - Mengyu Guo; Jin-Cheng Guo; Haodong Yao; Fene Gao; Lina Zhao; Lu Cai; Xuan Fan; Lin Bao; Xin Li; Xiaoyu Zhang; Mingdi Hu; Jie Mei; et al. (Science Bulletin, 2026)

Optimizing water and nitrogen management to balance yield and nitrogen loss in mechanically harvested low-stubble ratoon rice - Chaojie Lan; Hailong Xu; Bin Qin; Jinying Li; Bianhong Zhang; Jingnan Zou; Ting Chen; Jiahui Song; Zhihan Chen; Changxun Fang; Zhixing Zhang; Hongfei Chen; et al. (Field Crops Research, 2026)

Soil moisture and nutrient mobility influence nitrogen partitioning and translocation in maize (Zea mays L.) under various water-nitrogen regimes - Yuxin Chi; Shahid Ali; Jiahui Lin; Li Yang; Xunbo Zhou (European Journal of Agronomy, 2026)

Evaluation of the multi-scale variability of ocean bottom pressure in a global ocean general circulation model - Jiahui Bai; Jingwei Xie; Zipeng Yu; Jiangfeng Yu; Hailong Liu; Fan Yang; Pengfei Lin; Tao Zhang; Chunxiang Shi; Yun Xiao (Acta Oceanologica Sinica, 2026)

Public pension accelerates the household electrification: Experience from rural China - Lin Zhu; Hua Liao; Tunye Qiu; Jiahui Chen (Energy Policy, 2026)

Context-Dependent Regulation of Microglial Metabolic and Immune States via IL-3/CD123 Signaling: Implications for Glial Crosstalk and Cognitive Impairment - Zhongxu Yu; Yi Lin; Erming Yang; Xiaofei Ji; Jiahui Liu; Yang Jiao (Molecular Neurobiology, 2026)

Exploring the Role of B-Cell Biotherapy in Myasthenia Gravis from a Genetic Perspective: A Mendelian Randomization Study - Mengyuan Zhang; Cen Yue; Jie Fang; Jiahui Tang; Caihong Chen; Caili Zhou; Wanli Yang; Xingkai An; Qing Lin; Jiawei Zhang (Molecular Neurobiology, 2026)

The impact of sports mega-events on urban haze: the perspective of government environmental attention - Xiaoli Hu; Jiahui Ling; Shanlang Lin; Ruofei Lin (Environment, Development and Sustainability, 2025)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Microwave-driven catalytic upgrading of waste engine oil using defect-rich steel slag: Oxygen vacancy modulation and reaction mechanisms - Junhao Lin; Jiahui Hou; Jiashan Chen; Yanxi Liu; Yanan You; Mingxing Chen; Rui Ma; Hao Wang; Shichang Sun (Fuel, 2025)

Analysis of the odor profile and metabolome of traditional sea cucumber dishes: Multi-omics combined screening for molecular regulatory targets of process - Jiahui Song; Qiang Geng; Huihui Wang; Xu Zhang; Jian Jiao; Songyi Lin (Food Chemistry, 2025)

Exploration of the multi-dimensional quality deterioration patterns and mechanism analysis of sea urchin gonads during storage at ambient temperature - Jiahui Song; Qiang Geng; Yue Tang; Dong Chen; Songyi Lin (Food Chemistry, 2025)

Analysis of the mechanism of quality deterioration of egg yolk powder during storage from a multi-dimensional perspective - Yiding Yu; Jiahui Song; Jun Jiang; Songyi Lin (Food Chemistry, 2025)

Self-healing, highly stretchable, recyclable PU-curcumin elastomer with substrate-sensitive solid-state fluorescence - Linjie Wei; Xiubin Xu; Hongchun Mu; Wantong Lin; Jiahui Tang; Jieran Li; Jianwei Liu; Haitao Dong; Danfeng Yu; Xu Wu (Chemical Engineering Journal, 2025)

Efficient preparation of large-area anisotropic graphite films with high thermal conductivity and excellent electromagnetic shielding performance - Zhihong Han; Mingyi Tan; Daming Chen; Wenzheng Zhang; Zhipeng Lin; Jiahui Zhou; Yuhao Fang; Shengze Zhang; Qihong Wei; Xinghong Zhang; Wenbo Han (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Analysis of Genes Related to Cannabinoid Biosynthesis Pathways in Seed Hemp - Zuqing Yang; Huawei Wei; Xueqing Pan; Jiahui Chen; Huifan Kang; Yuxin Lin; Shaoqiang Jiang; Xuping Feng; Aifen Tao; Jianmin Qi; Jiantang Xu; Hongmei Kang; et al. (Tropical Plant Biology, 2025)

Unraveling the potential mechanism and prognostic value of pentose phosphate pathway in hepatocellular carcinoma: a comprehensive analysis integrating bulk transcriptomics and single-cell sequencing data - Bin Li; Tao Zeng; Cui Chen; Yuankai Wu; Shuying Huang; Jing Deng; Jiahui Pang; Xiang Cai; Yuxi Lin; Yina Sun; Yutian Chong; Xinhua Li; et al. (Functional & Integrative Genomics, 2025)

Seawater Flow-Freezing Characteristics in Open Container Injection Under Low-Temperature Conditions - Yuhao Fan; Bei Peng; Puyu Jiang; Jiahui Ren; Yuesen Lin; Longlong Gao; Baoren Li (Journal of Marine Science and Engineering, 2025)
The phenomenon of seawater flow-freezing exists during ballast water injection and drainage in polar vessels, but the heat transfer and ice evolution behaviors under low-temperature flow conditions remain unclear. This study developed a computational model for ballast tank freezing using the volume of fluid (VOF) and enthalpy–porosity method, and constructed a scaled experimental platform for the simulation model validation. Based on this model, the flow-heat transfer and ice evolution process in the ballast tank are analyzed in detail, with a focus on the influence of injection velocity, pipe diameter, and position on seawater freezing characteristics. The results show that during low-temperature water injection, phase change occurs preferentially in the tank bottom region, with ice presenting as a slurry morphology; when injection velocity increases from 0.25 m/s to 3.5 m/s, the maximum ice-phase volume fraction increases by 48.9%, indicating faster flow accelerates phase-change freezing; compared to other diameters, DN150 piping exhibits the highest turbulent kinetic energy (0.054 m2/s2) and the maximum shear stress (12.49 Pa), demonstrating optimal freezing resistance; compared to bottom injection, sidewall injection intensifies heat transfer/icing near tank walls and increases ice-clogging risk around ports. This study reveals intrinsic mechanisms of dynamic ice-blockage evolution, providing theoretical basis for anti-clogging design in polar ship systems.

GC-IMS and chemometrics identify critical flavor control points in egg yolk powder processing - Jiahui Song; Yaru Li; Fujun Guo; Songyi Lin; Zhijie Bao (Food Control, 2025)

Embryonic exposure to nanoplastics affects the metabolism and locomotor performance of a soil-dwelling, oviparous skink - Xinni He; Jiahui Xu; Shufang Zhang; Mengzhen Hu; Congcong Wang; Miao Guan; Peng Li; Lian Chen; Longhui Lin; Georgia Ward-Fear; Hong Li (Environmental Pollution, 2025)

The correlation between novel antidiabetic agents utilization and hepatocellular carcinoma incidence in type 2 diabetes patients: a network meta-analysis - Junjie Lin; Tianshu Ren; Qingchun Zhao; Qiang Tong; Jiahui Liu; Ye Kang; Yuan Yuan (European Journal of Clinical Pharmacology, 2025)

Study on soil improvement and microbial diversity restoration in metals-contaminated mining areas - Mingyu Xu; Yimei Zhang; Jiahui Zhao; Penghui Liu; Yi Pan; Wenting Lin; Acong Chen (Environmental Geochemistry and Health, 2025)

A remote sensing-based paradigm for revealing road ecological impacts in permafrost regions - Qingquan Sha; Jiawei Zhao; Lin Huang; Wei Cao; Jiahui Li; Liangxia Zhang; Yun Wang (Transportation Research Part D: Transport and Environment, 2025)

Research progress on the regulation of plant growth and development by TOR kinase - Jiahui Xu; Ying Zhang; Jiahong Qi; Haojia Shi; Xianwen Liu; Mei Jin; Qingyu Guo; Qian Wang; Kaiyue Wang; Yongpeng Li; Xigang Liu; Lin Guo; et al. (Plant Science, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

Cu-MOFs nanozyme with POD-like activity for the enrichment, identification, and intelligent colorimetric detection of omethoate - Xueer Lin; Jiahui Zou; Guancheng Zhu; Linfeng Pang; Yuqi Chen; Yanyan Huang (Food Bioscience, 2025)

The antibacterial activity and metabolomic analysis of the recombinant lectin protein PFL-96 derived from Pinctada fucata against Streptococcus agalactiae isolated from tilapia (Oreochromis niloticus) - Xiaojian Mo; Wenyue Li; Jianbing Liu; Qiting Li; Zhongxiu Liang; Xinyu Liang; Jiaxing Tang; Jiahui Liang; Jiang Lin; Peng Liu (Fish & Shellfish Immunology, 2025)

A strategy for enhancing mechanical properties of electrically controlled solid propellant via in-situ-induced microphase separation - Huimin Nai; Qiyang Wang; Yingxue Ju; Yangshun Ren; Jiahui Li; Jizeng Shang; Jian Zhang; Debin Xia; Ping Wang; Yulin Yang; Kaifeng Lin (Chemical Engineering Journal, 2025)

Effects of biofloc-electrochemical system on water quality, fish performance, and microbial diversity - Wenfei Su; Jincheng Lin; Wenchang Liu; Yanshuo Guo; Jiahui Wang; Guozhi Luo; Hongxin Tan (Aquacultural Engineering, 2025)

Interaction mechanisms of sea cucumber proteins with flavor compounds: Adsorption behavior, dynamic equilibrium and structural changes - Xinran Li; Jiahui Song; Jian Jiao; Qiang Geng; Songyi Lin (Food Chemistry, 2025)

Water flow-driven high piezo-photocatalytic efficacy in superthin and densely porous GO-TiO2/PVDF-HFP composite film for ROS generation - Jialin Zhuang; Yechen Wang; Liping Lin; Jiaying Xiao; Jiahui Cai; Yingmo Hu; Qi An (Chemical Engineering Journal, 2025)

Hybrid electrospun fibers with metal-based catalysts for zinc-air battery: Recent development and future perspectives - Mahmood ul Haq; Yongbiao Mu; Saz Muhammad; Baoxin Wu; Kejun Yan; Jiahui Luo; Zheng Li; Zhiqing Tang; Muhammad Ajmal; Wenjia Li; Lin Zeng (Chemical Engineering Journal, 2025)

Single cobalt atoms anchored on in-situ-formed carbon layers within restricted microenvironment: an efficient catalyst for oxygen evolution reaction - Yang Wang; Ying Zhou; Xuan-Yi Liu; Xiao-Qin Zheng; Shui-Jing Wang; Kai Zhang; Xiang-Bin Shao; Jiahui Kou; Lin-Bing Sun (Chemical Engineering Journal, 2025)

Water quality prediction at large-Scale: Systematic assessment of decomposition-deep learning models - Jiahui Shi; Lixiao Ni; Jiaming Liu; Hui Chen; Yushen Ma; Yi Zhang; Qingwei Lin; Zhen Zhang; Hang Xu; Yiping Li (Journal of Cleaner Production, 2025)

Growth behavior of heavy metal sulfide particles: A comparison between gas-liquid and liquid-liquid sulfidation - Chunxue Li; Meiqing Shi; Qingzhu Li; Jiahui Wu; Xu Yan; Qingwei Wang; Zhang Lin; Liyuan Chai (Journal of Environmental Sciences, 2025)

Unlocking the healing power of Jinhua white tea fermented by Eurotium cristatum using the unique “flowering” technology: A promising ally against inflammatory bowel disease - Yong Lin; Xirui Zhou; Silin Xie; Jian-an Huang; Jie Li; Yanyan Yao; Maiquan Li; Jiahui Bo; Lizheng Xiao; Zhonghua Liu; Wei Quan (Food Research International, 2025)

What we talk about when we talk about vegetarian diets: Insights into vegetarian practices in China - Zheng Chen; Jiahui Lin; Guojun Zeng (Appetite, 2025)

The simulation of the South China Sea by the variable resolution version of the global ocean general circulation model LICOM3.0 - Jiangfeng Yu; Jingwei Xie; Hailong Liu; Pengfei Lin; Zipeng Yu; Jiahui Bai (Ocean Modelling, 2025)

GC-IMS combined with multivariate statistical analysis: An efficient strategy for characterizing flavor components and assessing storage stability of egg yolk powder - Jiahui Song; Shuyun Chen; Songyi Lin; Fujun Guo; Zhijie Bao (Food Chemistry, 2025)

Nitrogen level determines arbuscular mycorrhizal fungi nitrogen uptake rate of Stipa purpurea in alpine steppe - Jiahui Sun; Yu Tang; Keyu Chen; Shijie Ren; Hailan Shi; Qiang Dong; Junfu Dong; Lin Zhang; Xiaoyong Cui; Yanfen Wang; Baoming Ji; Jing Zhang (Plant and Soil, 2025)

Exploring food-derived bioactive peptides: Efficacy, mechanisms, and clinical implications in ferroptosis regulation - Chenzhe Gao; Lin Zhang; Jiahui Ma; Haiyan Zhang; Yue Pang; Chenyu Xue; Dehai Li; Xiaoyu Zhao; Munkh-Amgalan Gantumur; Mizhou Hui; Weichen Hong; Yihong Bao; et al. (Trends in Food Science & Technology, 2025)

Designing advanced high-entropy alloy sensors for sensitive low-temperature acetone detection - Boyan Fu; Leyao Bi; Jiahui Lin; Junsheng Wen; Jiaxing Fu; Binglin Zou; Chunjie Wang; Yue Wang (Journal of Environmental Chemical Engineering, 2025)

RNA chaperone Hfq promotes the growth of Yersinia enterocolitica in refrigerated foods - Ming Liu; Xinyu Zhao; Zhi Wang; Ling Chen; Zimeng Wang; Huichan Zhai; Congyu Zhou; Huixian Wang; Yu Ding; Jumei Zhang; Xiuhua Lin; Jiahui Zeng; et al. (Food Microbiology, 2025)

Extracellular polymers substances towards the toxicity effect of Microcystis flos-aquae under subjected to nanoplastic stress - Jianhuang Su; Jiahui Lin; Wenlu Zhan; Jianjie Li; Xiuxian Dong; Tingting Zhang; Zaixian Yang; Zhuanxi Luo; Peiyong Guo (Environmental Pollution, 2025)

Embracing Internal States: A Review of Optimization of Repetitive Transcranial Magnetic Stimulation for Treating Depression - Tingting Wu; Qiuxuan Yu; Ximei Zhu; Yinjiao Li; Mingyue Zhang; Jiahui Deng; Lin Lu (Neuroscience Bulletin, 2025)

Deciphering the N1-substituent effects on biodegradation of sulfonamides: Novel insights revealed from molecular biology and computational chemistry approaches - Jiahui Hu; Ruiyang Li; Jiayu Zhang; Lijia Cao; Huaxin Lei; Renxin Zhao; Lin Lin; Xiao-yan Li; Wen Zhang; Bing Li (Water Research, 2025)

Glycerol-driven optimization of algae-bacteria symbiosis systems for enhanced lipid production and self-flocculation - Yuwei Zhang; Jiaheng Teng; Jiahui Huang; Liguo Shen; Hongjun Lin; Renjie Li; Xiang Cai; Zeqiong Xu; Meijia Zhang (Journal of Environmental Chemical Engineering, 2025)

Metagenomic assembly insight into the antibiotic resistance genes and antibiotic resistant bacteria in packaged drinking water system - Xiyang Xia; Qihui Gu; Ling Chen; Jumei Zhang; Weipeng Guo; Zhenjie Liu; Aimei Li; Xinhui Jiang; Meiqing Deng; Jiahui Zeng; Xiuhua Lin; Feiting Peng; et al. (Journal of Environmental Chemical Engineering, 2025)

Metagenomic analysis reveals the composition and sources of antibiotic resistance genes in coastal water ecosystems of the Yellow Sea and Yangtze River Delta - Xin Wang; Yude Lin; Shaoxuan Li; Jiahui Wang; Xiaohui Li; Demeng Zhang; Delin Duan; Zhanru Shao (Environmental Pollution, 2025)

Transformative effects of homo-valence ion doping on persistent luminescence nanophosphors for radiotherapy monitoring - Ziyun Miao; Pei Xu; Yurong Wei; Jiahui Tan; Zhenwei Liu; Jie Pan; Lin Shi; Yong Wang; Jie Wang (Chemical Engineering Journal, 2025)

Effects of hormones and digestive tract morphology on personality-driven foraging behaviour in the turtle Mauremys reevesii - Lin Gan; Jiahui Sun; Hong Li (Animal Behaviour, 2025)

Effective denitrification from landfill leachate using magnetic PVA/CMC/DE carrier immobilized microorganisms - Yunshuang Hu; Yufei Gu; Jiahui Tan; Chong Ding; Xinyi Yu; Zhixia Li; Hongfei Lin (Waste Management, 2025)

In situ sulfur-loaded on carbon materials for efficient antibiotic removal under visible light - Shouxin Zhu; Zhexiao Zhu; Jingyi Qu; Can Sun; Zijie Fang; Mingli Qin; Yangben Chen; Xiaolu Xu; Jiahui Lin; Min Liu; Hui Zheng (Journal of Water Process Engineering, 2025)

Precision-engineered bacterial nanovectors for synergetic co-delivery to harness cellular senescence and immunomodulation for enhanced tumor eradication - Zixuan Ye; Yuanzhuo Zhou; Lizhen Liang; Jiahui Zhao; Wenzheng Liu; Lingtong Meng; He Huang; Jingpeng Yang; Xinping Lin; Yanan Li (Chemical Engineering Journal, 2025)

Memory Reconsolidation Updating in Substance Addiction: Applications, Mechanisms, and Future Prospects for Clinical Therapeutics - Shihao Huang; Xiaoxing Liu; Zhonghao Li; Yue Si; Liping Yang; Jiahui Deng; Yixiao Luo; Yan-Xue Xue; Lin Lu (Neuroscience Bulletin, 2025)

Emerging role of adaptive immunity in diabetes-induced cognitive impairment: from the periphery to the brain - Genhui Yang; Runtao Su; Jie Bu; Ying Li; Xueling Lin; Jiahui Jin; Yanjun Zhang; Pengwei Zhuang; Hong Guo; Qingsheng Yin (Metabolic Brain Disease, 2025)

Inclusion Complex of Nimodipine with Sulfobutylether-β-cyclodextrin: Preparation, Characterization, In Vitro and In Vivo Evaluation - Jiahui Liu; Meichai Li; Yongjie Huang; Xinyu Wang; Youfa Xu; Zhiqin Fu; Zhizhe Lin; Jianming Chen; Xin Wu (AAPS PharmSciTech, 2025)

Multifunctional nanofiber system with photothermal-controlled drug delivery and motion monitoring capabilities as intelligent wound dressing - Peiran Lin; Kaitong He; Jiahui Luo; Jiyuan Wang; Yuting Liu; Jian Zhang; Hao Fan; Shunfen Huang; Wei Lan; Wenlong Wang; Xuhui Zhang; Botao Gao; et al. (Chemical Engineering Journal, 2025)

Microbial rrn copy number is associated with soil C: N ratio and pH under long-term fertilization - Xiu Wang; Jiahui Lin; Xinyi Peng; Yifan Zhao; Haodan Yu; Kankan Zhao; Albert Barberán; Yakov Kuzyakov; Zhongmin Dai (Science of The Total Environment, 2024)

Lysosome-localization and tumor-targeting of novel photosensitizers enhance the ablation of cancer - Jiahui Li; Guodong Wang; Yuhan Mai; Wei Zhang; Hailong Zhao; Yang Zhou; Liyun Chen; Yuxin Lin; Longguang Jiang; Peng Xu; Xiaolei Zhou; Cai Yuan; et al. (Journal of Photochemistry and Photobiology B: Biology, 2024)

Hydrocyclone-induced classification reduction and spin desorption of contaminated soil remediation with heavy metal and organics - Yi Liu; Jiahui Ren; Kai Ma; Jianping Li; Pengbo Fu; Kuangfei Lin; Hualin Wang (Journal of Hazardous Materials, 2024)

High-valent iron–oxo species in heterogeneous catalysis: Formation, mechanism, and reactivity for the degradation of various emerging organic contaminants - Yin Li; Jiahui Hu; Yutian Bao; Yanan Xiao; Lin Lin; Bing Li; Xiao-yan Li (Chemical Engineering Journal, 2024)

The role of mitochondrial dysfunction in the association between trace metals and QTc prolongation in the aged population - Jiahui Wang; Peiyi Liu; Yankui Lin; Xia Zhang; Lingling Lin; Fengqi Wu; Ying Fu; Desheng Wu; Xiaohu Ren; Haiyan Huang; Xifei Yang; Jianjun Liu (Science of The Total Environment, 2024)

CircCDR1as orchestrates the advancement of asthma triggered by PM2.5 through the modulation of ferroptosis - Yu Cheng; Haimin Zhang; Boyu Guan; Yong Zhang; Chuhao Qin; Dongsheng Li; Jiahui Zhang; Boyu Zhang; Yingwei Lin; Fasheng Li (Science of The Total Environment, 2024)

Effective strategies alleviate mitochondrial toxicity of perfluorooctanoic acid: Modification of functional head group and inhibition of toxic target - Ruijia Zhang; Lanyin Tu; Yingshi Lin; Jiahui Liu; Tong Liang; Wenhua Lu; Baowei Chen; Tiangang Luan (Journal of Hazardous Materials, 2024)

Copper-based photocatalysts with natural organic ligands for efficient removal of tetracycline under visible light - Shouxin Zhu; Can Sun; Zhexiao Zhu; Jingyi Qu; Zijie Fang; Yangben Chen; Jiahui Lin; Xiaolu Xu; Miaoyan Cheng; Min Jiang; Hui Zheng (Journal of Environmental Management, 2024)

Dynamic water migration and flavor analysis of sea cucumber in the process of Sichuan pepper seasoning soak - Jiahui Song; Xinran Li; Pengfei Jiang; Songyi Lin (Food Chemistry, 2024)

Ginkgo biloba leaf polysaccharide-stabled selenium nanozyme as an efficient glutathione peroxidase mimic for the preservation of bananas and cherry tomatoes - Jiahui Zou; Huimin Zhong; Cong Jiang; Guancheng Zhu; Xueer Lin; Yanyan Huang (Food Chemistry, 2024)

3D printed microplasma optical emission spectrometry coupled with ZIF-8 based dispersive solid-phase extraction for field analysis of waterborne arsenic - Jiahui Yang; Yao Lin; Xi Wang; Yuanyuan Li; Yurong Deng; Chengbin Zheng (Analytica Chimica Acta, 2024)

Generation of canine neutralizing antibodies against canine parvovirus by single B cell antibody technology - Zhihao Wang; Pengfei Shi; Sheng Wang; Zhipeng Lin; Zhichen Wang; Chengguang Zhang; Ling Zhao; Sizhu Suolang; Jiahui Zou; Hongbo Zhou (Archives of Virology, 2024)

The role and function mechanism of tapP in modulating the virulence of Aeromonas hydrophila - Rui Long; Jinming Wei; Caijiang Xiong; Bei Wang; Jiahui Lu; Hua Ye; Yun Li; Yongyao Yu; Lingyun Lin; Ronghua Wu (Aquaculture, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Study on the adsorption and migration rule of Sichuan pepper characteristic volatile compounds during the cooking process in the sea cucumber body wall - Jiahui Song; Xinran Li; Dong Chen; Songyi Lin (Food Chemistry, 2024)

The role of aroA and ppk1 in Aeromonas veronii pathogenicity and the efficacy evaluation of mutant strain AV-ΔaroA/ppk1 as a live attenuated vaccine - Jiahui Lu; Wan'e Ding; Jinming Wei; Hua Ye; Hui Luo; Yun Li; Ying Lin; Yongyao Yu; Jiayun Yao; Ronghua Wu (Fish & Shellfish Immunology, 2024)

Structural characterisation and anti-colon cancer activity of an arabinogalactan RSA-1 from Raphani semen - Qi Li; Shuang Jiang; Qianbo Wang; Jiahui Sun; Zhibin Wang; Xiaotong Wang; Xuepeng Shi; Yuanqiu Mu; Lin Wei; Chunjuan Yang (Carbohydrate Polymers, 2024)

Organic carbon inputs shift the profiles of phosphorus cycling-related genes in maize rhizosphere - Yanlan Huang; Jiahui Lin; Caixian Tang; Jianming Xu (Plant and Soil, 2024)

Phylogenetic analysis, genetic diversity, and epidemiology of pigeon paramyxovirus type 1 in China - Chuqi Huang; Shaoyu Tu; Wei Sheng; Zhihao Wang; Zhipeng Lin; Jing Qian; Jiahui Zou; Hongbo Zhou (Archives of Virology, 2024)

Heating–cooling–heating cycles within ca. 70 Myr recorded in UHT granulites in the Khondalite Belt, North China Craton - Yang Qi; Shujuan Jiao; Lin Chen; Jiahui Liu; Yu Liu; Jinghui Guo (Precambrian Research, 2024)

Autophagy aggravates multi-walled carbon nanotube-induced ferroptosis by suppressing PGC-1 dependent-mitochondrial biogenesis in lung epithelial cells - Lin Zhu; Deyu Zhu; Jiahui Ran; Maojie Li; Zhebin Lai; Yan Zhou; Lei Luo; Xiliang Liu; Kanmin Mao; Kunming Tian (Chemico-Biological Interactions, 2024)

Effects of a dual functional filler, polyethersulfone-g-carboxymethyl chitosan@MWCNT, for enhanced antifouling and penetration performance of PES composite membranes - Jiahui Zhao; Dahai Zeng; Qiwei Wang; Zhidan Lin; Florian Vogel; Wei Li; Peng Zhang (Journal of Environmental Management, 2024)

Nanoplastic pollution changes the intestinal microbiome but not the morphology or behavior of a freshwater turtle - Shuo Gao; Shufang Zhang; Jiahui Sun; Xinni He; Shaoshuai Xue; Wenyi Zhang; Peng Li; Longhui Lin; Yanfu Qu; Georgia Ward-Fear; Lian Chen; Hong Li (Science of The Total Environment, 2024)

High-resolution and real-time wastewater viral surveillance by Nanopore sequencing - Xiaoqing Xu; Yu Deng; Jiahui Ding; Qinling Tang; Yunqi Lin; Xiawan Zheng; Tong Zhang (Water Research, 2024)

Strong adsorption enhanced nitrogen removal from landfill leachate by PVA/CMC/WPU pellets immobilized microorganisms - Jiahui Tan; Yunshuang Hu; Chong Ding; Yuyu Li; Yufei Gu; Zhixia Li; Hongfei Lin (Journal of Water Process Engineering, 2024)

Structural engineering of magnetite nanozymes for enhanced chemodynamic cancer therapy - Yong Qian; Jinglu Zou; Jiahui Zhang; Xingyu Wang; Xiangfu Meng; Yefeng Lin; Wenchu Lin; Miqin Zhang; Hui Wang (Chemical Engineering Journal, 2024)

Ozone-delivering nanocomposite hydrogel for acute Staphylococcus aureus osteomyelitis treatment via neutrophil regulation - Hangtian Wu; Yihuang Lin; Yanpeng Lin; Mingye Deng; Jiahui Hou; Dahai Liu; Zhuang Cui; Daogang Guan; Jun Wang; Bin Yu (Chemical Engineering Journal, 2024)

Mathematical derivation and mechanism analysis of beta oscillations in a cortex-pallidum model - Minbo Xu; Bing Hu; Zhizhi Wang; Luyao Zhu; Jiahui Lin; Dingjiang Wang (Cognitive Neurodynamics, 2024)

Nutritional activities of luteolin in obesity and associated metabolic diseases: an eye on adipose tissues - Zhixin Zhang; Jiahui Wang; Yan Lin; Juan Chen; Jian Liu; Xian Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Blockade of aryl hydrocarbon receptor restricts omeprazole-induced chronic kidney disease - Nan Sun; Yimeng Zhang; Lin Ding; Xin An; Fang Bai; Yanjiang Yang; Kuipeng Yu; Jiahui Fan; Lei Liu; Huimin Yang; Xiangdong Yang (Journal of Molecular Medicine, 2024)

Mechanism of peroxymonosulfate activation by nanoparticle Co@N–C: Experimental investigation and theoretical calculation - Mu Li; Lin Lin; Wei Zhang; Yubin Zou; Jiahui Hu; Yin Li; Bing Li; Feiyun Sun; Xiao-yan Li (Chemosphere, 2024)

Toosendanin induces hepatotoxicity by restraining autophagy and lysosomal function through inhibiting STAT3/CTSC axis - Li Luo; Jiajie Ni; Jiahui Zhang; Jinxian Lin; Sixin Chen; Feihai Shen; Zhiying Huang (Toxicology Letters, 2024)

Predicting the binding configuration and release potential of heavy metals on iron (oxyhydr)oxides: A machine learning study on EXAFS - Junqin Liu; Jiang Zhao; Jiapan Du; Suyi Peng; Jiahui Wu; Wenchao Zhang; Xu Yan; Zhang Lin (Journal of Hazardous Materials, 2024)

Trace Co(II) triggers peracetic acid activation in phosphate buffer: New insights into the oxidative species responsible for ciprofloxacin removal - Feifei Liu; Yubin Zou; Hebin Liang; Jiahui Hu; Yin Li; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2024)

Design, synthesis and mechanism study of coumarin-sulfonamide derivatives as carbonic anhydrase IX inhibitors with anticancer activity - Qianqian Lv; Jing Zhang; Jianghong Cai; Lexian Chen; Jiajie Liang; Tianwan Zhang; Jiahui Lin; Ruiyao Chen; Zhiling Zhang; Peiting Guo; Yue Hong; Lingxue Pan; et al. (Chemico-Biological Interactions, 2024)

Community Structure and Water Quality Assessment of Benthic Macroinvertebrates in Hongze Lake - Lixiao Ni; Lin Zhou; Amar Ali Adam Hamad; Chu Xu; Wenlu Sang; Cunhao Du; Yun Nie; Haoyue Li; Jiahui Shi; Shiyin Li (Bulletin of Environmental Contamination and Toxicology, 2024)

Effect of characteristic parameters of air-bleeding/blowing interface on tunnel pressure waves in streamlined regions of high-speed trains: A numerical simulation study - Kailong Jin; Lin Zhang; Xinzhe Li; Lindong Li; Jiahui Chen; Jinke Wang; Jiqiang Niu (Sustainable Cities and Society, 2024)

Multiphase flow and reactor optimization of a 1MWth pilot-scale circulating fluidized bed for coal staged conversion - Yuxin Ge; Jiahui Yu; Junjie Lin; Shuai Wang; Kun Luo; Qinhui Wang; Jianren Fan (Chemical Engineering Journal, 2024)

Long-Term Effects of Ecological Restoration Projects on Ecosystem Services and Their Spatial Interactions: A Case Study of Hainan Tropical Forest Park in China - Jiahui Zhong; Linlin Cui; Zhiyin Deng; Yong Zhang; Jie Lin; Geng Guo; Xiang Zhang (Environmental Management, 2024)

Effect of suspended particulate matter on physiological, biochemical and photosynthetic characteristics of Chlorella pyrenoidosa in the Jinjiang Estuary (Fujian, China) - Jiahui Lin; Jie Liu; Hui Xing; Sijia Chen; Yiting Nan; Junming He; Bo Hu; Yanfang Wei; Peiyong Guo (Ecotoxicology, 2024)

The characteristic terpenes in sea cucumber soaked in star anise solution were characterized by HS-SPME-GC–MS and PCA analysis - Xinran Li; Pengfei Jiang; Jiahui Song; Songyi Lin (Food Chemistry, 2024)

Study on the differences in flavor adsorption ability of sea cucumber each part based on HS-SPME-GC-MS - Jiahui Song; Xinran Li; Dong Chen; Songyi Lin (Food Bioscience, 2024)

Optimizing waste molasses utilization to enhance electron transfer via micromagnetic carriers: Mechanisms and high-nitrate wastewater denitrification performance - Jiahui Chen; Yi Xue; Dongli Yang; Sijia Ma; Yuan Lin; Haiyue Wang; Yanru Wang; Hongqiang Ren; Ke Xu (Environmental Research, 2024)

Genetic Diversity and Population Structure of Chinese Longsnout Catfish (Leiocassis longirostris) Using Microsatellite DNA Markers - Yanling Hou; Huan Ye; Xinhua Song; Jiahui Fan; Junyi Li; Jian Shao; Yizhou Wang; Danqing Lin; Huamei Yue; Rui Ruan; Chuangju Li (Fishes, 2024)
The Chinese longsnout catfish (Leiocassis longirostris) is an economically important freshwater fish in China; however, its wild resources have declined dramatically in recent decades. Understanding the genetic structure of Chinese longsnout catfish populations is crucial to guide breeding programs and fishy restoration. In this study, 15 highly polymorphic microsatellite DNA loci were used to evaluate its genetic diversity and population structure. Chinese longsnout catfish populations show high genetic diversity; they do not show significant genetic differentiation or systematic geographic pattern of variation. From the upper to the lower reaches of the Yangtze River, the genetic diversity of Chinese longsnout catfish populations showed an increasing trend. The Gezhouba and Three Gorges dams, which physically divide the Yangtze River into upstream and mid-downstream sections, did not contribute to the genetic differentiation of Chinese longsnout catfish populations. Hence, the source of broodstock is not critical for within-river breeding programs and stock enhancement to restore the wild population. In addition, possible effects of dams on differentiation among populations are crucial and long-term evaluation is essential.

Effect of human chorionic gonadotrophin (HCG) and luteinizing hormone releasing hormone A3 (LHRH-A3) on reproduction and development of brood pouch in Hippocampus erectus - Xuange Liu; Gongpei Wang; Jiahui Chen; Sheng Bi; Chenlei Huang; Han Lai; Huadong Yi; Haiyang Li; Qiuxian Chen; Li Lin; Zhilun Zhang; Xuchong Wei; et al. (Aquaculture, 2024)

Contrasting lake changes in Tibet revealed by recent multi-modal satellite observations - Jiangjun Ran; Lin Liu; Guoqing Zhang; C.K. Shum; Jiahui Qiu; Ruigang Hu; Jianping Li; Junhuan Peng; Cheinway Hwang; Yi Luan; Yue Sun; Min Xu; et al. (Science of The Total Environment, 2024)

Carbon potential of China's Grain to Green Program and its contribution to the carbon target - Yinqiu Ma; Lin Huang; Jiahui Li; Wei Cao; Yumei Cai (Resources, Conservation and Recycling, 2024)

Permafrost on the Tibetan Plateau is degrading: Historical and projected trends - Tongqing Shen; Peng Jiang; Qin Ju; Jiahui Zhao; Xuegao Chen; Hui Lin; Bin Yang; Changhai Tan; Ying Zhang; Xinting Fu; Zhongbo Yu (Journal of Hydrology, 2024)

Preparation of refined phosphoric acid with recycling of raffinate acid by the extraction of metal impurities - Xiaokang Gong; Chao Hu; Yanru Jin; Haifeng Liu; Jiahui Bai; Lixue Niu; Lin Yang (Journal of Cleaner Production, 2024)

Benefits, potential and risks of China's grassland ecosystem conservation and restoration - Jiahui Li; Lin Huang; Wei Cao; Jian Wang; Jiangwen Fan; Xinliang Xu; Haijing Tian (Science of The Total Environment, 2023)

Levels of iron and iron-related proteins in Alzheimer’s disease: A systematic review and meta-analysis - Lin Gong; Jiahui Sun; Shuyan Cong (Journal of Trace Elements in Medicine and Biology, 2023)

Deterministic factors modulating assembly of groundwater microbial community in a nitrogen-contaminated and hydraulically-connected river-lake-floodplain ecosystem - Zhiyuan Qiao; Yizhi Sheng; Guangcai Wang; Xianglong Chen; Fu Liao; Hairu Mao; Hongyu Zhang; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Journal of Environmental Management, 2023)

Structural characteristics of zooplankton communities in Hongze Lake driven by water environmental factors from 2016 to 2020 - Lixiao Ni; Haoyue Li; Lin Zhou; Jiahui Shi; Yun Nie; Feng Zhao; Shiyin Li (Environmental Monitoring and Assessment, 2023)

A general characterization of integrating and querying heterogeneous fuzzy spatiotemporal XML data - Lin Zhu; Jiahui Wang; Luyi Bai (Earth Science Informatics, 2023)

Multifunctional regulation of NADPH oxidase in growth, microsclerotia formation and virulence in Metarhizium rileyi - Liqin Fan; Bingjie Li; Jiahui Wang; Xinxin Li; Feilong Ma; Fang Du; Hongli Li; Yunlong Lin (Biotechnology Letters, 2023)

Frozen carbon is gradually thawing: Assessing interannual dynamics of thawed soil organic carbon stocks in the Tibetan Plateau permafrost area from 1901−2020 - Tongqing Shen; Peng Jiang; Qin Ju; Xuegao Chen; Hui Lin; Jiahui Zhao; Fan Zhang; Zhongbo Yu (Agricultural and Forest Meteorology, 2023)

Optimizing aeration intensity to enhance self-flocculation in algal-bacterial symbiosis systems - Jiahui Huang; Sihan Cheng; Yuwei Zhang; Jiaheng Teng; Meijia Zhang; Hongjun Lin (Chemosphere, 2023)

Selective adsorption of 1-hydroxyethylidene-1,1-diphosphonic acid on calcite surface in smithsonite flotation system - Jiahui Wu; Longhua Xu; Donghui Wang; Kai Xue; Xinzhang Shi; Lin Peng; Jiushuai Deng (Minerals Engineering, 2023)

L-theanine regulates the immune function of SD rats fed high-protein diets through the FABP5/IL-6/STAT3/PPARα pathway - Yangling Zhang; Yuxin Song; Jiao Zhang; Lanlan Li; Lin He; Jiahui Bo; Zhihua Gong; Wenjun Xiao (Food and Chemical Toxicology, 2023)

MOF@Polydopamine-incorporated membrane with high permeability and mechanical property for efficient fouling-resistant and oil/water separation - Jiahui Zhao; Lin Cao; Xiao Wang; Haoling Huo; Huaijun Lin; Qiwei Wang; Xusheng Yang; Florian Vogel; Wei Li; Zhidan Lin; Peng Zhang (Environmental Research, 2023)

Manipulating critical memory periods to treat psychiatry disorders - Jiahui Deng; Xiao Lin; Yongbo Zheng; Sizhen Su; Xiaoxing Liu; Kai Yuan; Le Shi; Yanping Bao; Lin Lu (Science Bulletin, 2023)

A review on research progress in photocatalytic degradation of organic pollutants by Bi2MoO6 - Zhaoxin Lin; Jie Xu; Huijie Gu; Jiayi Huang; Jiahui Lin; Jing Shao; Dandan Wang; Hongji Li (Journal of Environmental Chemical Engineering, 2023)

Constructing zinc single-atom catalysts for the direct electron-transfer mechanism in peroxymonosulfate activation to degrade sulfamethoxazole efficiently - Yanan Xiao; Jiahui Hu; Xiao-yan Li; Yubin Zou; Yin Li; Lin Lin; Bing Li (Chemical Engineering Journal, 2023)

Causal relationships between chronotype and risk of multiple cancers by using longitudinal data and Mendelian randomization analysis - Shanshan Tian; Longtao Huangfu; Sizhi Ai; Junwei Zheng; Le Shi; Wei Yan; Ximei Zhu; Qianwen Wang; Jiahui Deng; Yanping Bao; Suhua Chang; Lin Lu (Science China Life Sciences, 2023)

Transient neonatal hyperglycemia induces metabolic shifts in the rat hippocampus: a 1H NMR-based metabolomics analysis - Yinli Huang; Junli Chen; Jiahui Lu; Hanqi Luo; Na Ying; Wei Dong; Minjie Lin; Hong Zheng (Metabolic Brain Disease, 2023)

Heavy metal contamination collapses trophic interactions in the soil microbial food web via bottom-up regulation - Xuehua Wang; Zhongmin Dai; Jiahui Lin; Haochun Zhao; Haodan Yu; Bin Ma; Lingfei Hu; Jiachun Shi; Xiaoyun Chen; Manqiang Liu; Xin Ke; Yijun Yu; et al. (Soil Biology and Biochemistry, 2023)

Periodate activation by atomically dispersed Mn on carbon nanotubes for the production of iodate radicals and rapid degradation of sulfadiazine - Jiahui Hu; Yubin Zou; Yin Li; Zehui Yu; Yutian Bao; Lin Lin; Bing Li; Xiao-yan Li (Chemical Engineering Journal, 2023)

Microwave-catalyzed pyrolysis of waste engine oil using steel slag catalyst: Structure design and insights into the intrinsic mechanism of active catalytic sites and microwave absorption functions - Jiahui Hou; Junhao Lin; Lin Fang; Xi Zhang; Rui Ma; Juan Luo (Chemical Engineering Journal, 2023)

Simultaneous recovery of Fe2O3 and PbCl2 from hazardous jarosite residues via hydrothermal phase transformation with NaCl - Yejing Zeng; Wenchao Zhang; Jiahui Wu; Yangjin Wei; Yong Ke; Meiqing Shi; Xu Yan; Zhang Lin (Hydrometallurgy, 2023)

Changes in soil Cd contents and microbial communities following Cd-containing straw return - Haojie Xu; Yu Huang; Xinquan Xiong; Hang Zhu; Jiahui Lin; Jiachun Shi; Caixian Tang; Jianming Xu (Environmental Pollution, 2023)

Application of Human Stem Cell Derived Retinal Organoids in the Exploration of the Mechanisms of Early Retinal Development - Jiahui Kang; Jing Gong; Cao Yang; Xi Lin; Lijuan Yan; Yu Gong; Haiwei Xu (Stem Cell Reviews and Reports, 2023)

Nitrogen species and microbial community coevolution along groundwater flowpath in the southwest of Poyang Lake area, China - Xianglong Chen; Guangcai Wang; Yizhi Sheng; Fu Liao; Hairu Mao; Bo Li; Hongyu Zhang; Zhiyuan Qiao; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Chemosphere, 2023)

Microplastic exposure induces muscle growth but reduces meat quality and muscle physiological function in chickens - Jiahui Chen; Genghua Chen; Haoqi Peng; Lin Qi; Danlu Zhang; Qinghua Nie; Xiquan Zhang; Wen Luo (Science of The Total Environment, 2023)

Orally administered BZL-sRNA-20 oligonucleotide targeting TLR4 effectively ameliorates acute lung injury in mice - Dandan Zhao; Yuhao Qin; Jiaqi Liu; Kegong Tang; Shuaiyao Lu; Zirui Liu; Yexuan Lin; Cong Zhang; Fengming Huang; Jiahui Chang; Chang Li; Mingyao Tian; et al. (Science China Life Sciences, 2023)

Confined self-assembly of S, O co-doped GCN short nanotubes/EG composite towards HMIs electrochemical detection and removal - Jue Wang; Kan Kan; Ping Yu; Yihe Fan; Jiahui Fan; Lin Jiang; Fangjie Qin; Keying Shi (Journal of Hazardous Materials, 2023)

Paleoproterozoic accretion and assembly of the Western Block of North China: A new model - Changqing Yin; Guochun Zhao; Wenjiao Xiao; Shoufa Lin; Rui Gao; Jian Zhang; Jiahui Qian; Peng Gao; Hengzhong Qiao; Wenxuan Li (Earth-Science Reviews, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

TRFM-LS: Transformer-Based Deep Learning Method for Vessel Trajectory Prediction - Dapeng Jiang; Guoyou Shi; Na Li; Lin Ma; Weifeng Li; Jiahui Shi (Journal of Marine Science and Engineering, 2023)
In the context of the rapid development of deep learning theory, predicting future motion states based on time series sequence data of ship trajectories can significantly improve the safety of the traffic environment. Considering the spatiotemporal correlation of AIS data, a trajectory time window panning and smoothing filtering method is proposed for the abnormal values existing in the trajectory data. The application of this method can effectively deal with the jump values and outliers in the trajectory data, make the trajectory smooth and continuous, and ensure the temporal order and integrity of the trajectory data. In this paper, for the features of spatiotemporal data of trajectories, the LSTM structure is integrated on the basis of the deep learning Transformer algorithm framework, abbreviated as TRFM-LS. The LSTM module can learn the temporal features of spatiotemporal data in the process of computing the target sequence, while the self-attention mechanism in Transformer can solve the drawback of applying LSTM to capture the sequence information weakly at a distance. The advantage of complementarity of the fusion model in the training process of trajectory sequences with respect to the long-range dependence of temporal and spatial features is realized. Finally, in the comparative analysis section of the error metrics, by comparing with current state-of-the-art methods, the algorithm in this paper is shown to have higher accuracy in predicting time series trajectory data. The research in this paper provides an early warning information reference for autonomous navigation and autonomous collision avoidance of ships in practice.

Mitigating soil salinity stress with titanium gypsum and biochar composite materials: Improvement effects and mechanism - Xin Xu; Jiahui Wang; Yiming Tang; Xuedan Cui; Daibing Hou; Hongjun Jia; Shaobo Wang; Lin Guo; Jinhang Wang; Aijun Lin (Chemosphere, 2023)

Biofouling-resistant polyamidoxime-based natural hierarchical porous bamboo strips prepared by in-situ polymerization for uranium extraction from seawater - Ying Wang; Zaiwen Lin; Jing Yu; Jiahui Zhu; Jingyuan Liu; Qi Liu; Rongrong Chen; Peili Liu; Jun Wang (Journal of Environmental Chemical Engineering, 2023)

Rapid and sensitive quantification of cyclamate in beverages by miniature microplasma optical emission spectrometry - Jiang Jing; Siyu He; Jiahui Yang; Rui Yang; Yao Lin; Chengbin Zheng (Food Chemistry, 2023)

A rapid, high-throughput, and sensitive PEG-precipitation method for SARS-CoV-2 wastewater surveillance - Xiawan Zheng; Mengying Wang; Yu Deng; Xiaoqing Xu; Danxi Lin; Yulin Zhang; Shuxian Li; Jiahui Ding; Xianghui Shi; Chung In Yau; Leo L.M. Poon; Tong Zhang (Water Research, 2023)

Campylobacter jejuni infection induces dynamic expression of avian host defense peptides in vitro and in vivo - Pengxiang Li; Yifang Cui; Fangfang Guo; Jiahui Guo; Xiaoya Cao; Jun Lin; Baoan Ding; Fuzhou Xu (Veterinary Microbiology, 2023)

Bacterial coculture enhanced Cd sorption and As bioreduction in co-contaminated systems - Huaiting Liu; Zhiqi Hong; Jiahui Lin; Dan Huang; Lena Q. Ma; Jianming Xu; Zhongmin Dai (Journal of Hazardous Materials, 2023)

Fast pyrolysis of algae model compounds for bio-oil: In-depth insights into the volatile interaction mechanisms based on DFT calculations - Donghua Xu; Junhao Lin; Rui Ma; Jiahui Hou; Shichang Sun; Ning Ma (Fuel, 2023)

Catalytic activity enhancement by P and S co-doping of a single-atom Fe catalyst for peroxymonosulfate-based oxidation - Yin Li; Jiahui Hu; Yubin Zou; Lin Lin; Hebin Liang; Huaxin Lei; Bing Li; Xiao-yan Li (Chemical Engineering Journal, 2023)

Sediment and interstitial water heavy metals in mangrove restoration wetland and preliminary exploration of microplastics in interstitial water - Bo Hu; Jiahui Lin; Junming He; Meiyan Zheng; Jinyang Wang; Yiting Nan; Yaqing Wu; Peiyong Guo (CATENA, 2023)

Mitigation of protein fouling by magnesium ions and the related mechanisms in ultrafiltration process - Hui Zou; Jiahui Huang; Meijia Zhang; Hongjun Lin; Jiaheng Teng; Zhengyi Huang (Chemosphere, 2023)

An influencing mechanism for ecological asset gains and losses and its optimization and promotion pathways in China - Jiahui Li; Lin Huang; Wei Cao (Journal of Geographical Sciences, 2022)

Inhibition of BETs prevents heat shock-induced cell death via upregulating HSPs in SV40 large T antigen transfected cells - Nan Zhou; Ye Zhang; Gongyun Lei; Yifan Chen; Ting Lin; Qin Liu; Yinshuang Zhao; Jiahui Mao; Yongying Jiang; Renfang Mao (Genes & Genomics, 2022)

Spatio-temporal variations in ecological spaces and their ecological carrying status in China’s mega-urban agglomerations - Shihao Wang; Lin Huang; Xinliang Xu; Jiahui Li (Journal of Geographical Sciences, 2022)

Effects of Suspended Particles on Exopolysaccharide Secretion of Two Microalgae in Jinjiang Estuary (Fujian, China) - Jie Liu; Xiaoyu Han; Hui Xing; Yiting Nan; Jiahui Lin; Junming He; Sijia Chen; Yanfang Wei; Peiyong Guo (Journal of Marine Science and Engineering, 2022)
The effects of suspended particles (SP) of different concentrations and sizes on the secretion of exopolysaccharide (EPS) by Chlorella pyrenoidosa (C. pyrenoidosa) and Microcystis flos-aquae (M. flos-aquae) in Jinjiang Estuary, Fujian Province, China were studied in co-cultures of microalgae and SP. The results show that the SP concentration has an “inhibit–promote–inhibit” effect on the secretion of EPS by C. pyrenoidosa, whereby there is an optimal concentration of SP corresponding to the largest amount of EPS secreted by C. pyrenoidosa. Low concentrations had no significant effect on the secretion of EPS from M. flos-aquae (p > 0.05), whereas higher concentrations had an inhibitory effect. The C. pyrenoidosa EPS content was found to be significantly decreased in response to SP of small particle sizes (0–75 and 75–120 μm) and significantly increased for SP of large particle sizes (120–150 and 150–500 μm). Small particle sizes (0–75 and 75–120 μm) were found to be beneficial to the secretion of EPS from M. flos-aquae, and the promotion of EPS secretion gradually decreased with the increase in SP particle size. However, when the particle size was too large (120–150 and 150–500 μm), SP had no significant effect on EPS secretion. This study is helpful for understanding the microalgae EPS secretion response to SP and provides a scientific basis for studying the mechanism of EPS secretion by algae and the effect of SP on eutrophication of the estuary.

Consistent responses of microbial C and N metabolic processes to elevated CO2 across global terrestrial ecosystems - Jiahui Lin; Yanlan Huang; Haochun Zhao; Mengjie Yu; Weiqin Su; Huaihai Chen; Peng Leng; Jihui Li; Yu Luo; Yong Li; Zhongmin Dai; Jianming Xu (Journal of Soils and Sediments, 2022)

Dimeric hexylitaconic acids from the marine-derived fungus Aspergillus welwitschiae CUGBMF180262 - Jiahui Han; Na Yang; Shangzhu Wei; Jia Jia; Rui Lin; Jiangpeng Li; Hongkai Bi; Fuhang Song; Xiuli Xu (Natural Product Research, 2022)

Persistent pollution episodes, transport pathways, and potential sources of air pollution during the heating season of 2016–2017 in Lanzhou, China - Yongtao Guo; Chunying Lin; Jiangping Li; Lingbo Wei; Yuxia Ma; Qidong Yang; Dandan Li; Hang Wang; Jiahui Shen (Environmental Monitoring and Assessment, 2021)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Ecological treatment technology for agricultural non-point source pollution in remote rural areas of China - Xuesong Yi; Dexin Lin; Jiahui Li; Jie Zeng; Dexin Wang; Fei Yang (Environmental Science and Pollution Research, 2021)

Assessing the spatiotemporal impact of climate change on event rainfall characteristics influencing landslide occurrences based on multiple GCM projections in China - Qigen Lin; Ying Wang; Thomas Glade; Jiahui Zhang; Yue Zhang (Climatic Change, 2020)

Research on Gas Outburst Coal Seam Mining Technology Based on the Theory of Gob-Side Entry Retaining - Yongkui Shi; Xin Wang; Jian Hao; Jiahui Lin; Weijia Cheng; Jun Chen; Xiao Li (Geotechnical and Geological Engineering, 2020)

Early secreted antigenic target of 6-kDa of Mycobacterium tuberculosis promotes caspase-9/caspase-3-mediated apoptosis in macrophages - Jiahui Lin; Qun Chang; Xueting Dai; Dan Liu; Yuyin Jiang; Yalei Dai (Molecular and Cellular Biochemistry, 2019)

In vitro remodeling and structural characterization of degradable polymer scaffold-based tissue-engineered vascular grafts using optical coherence tomography - Wanwen Chen; Junqing Yang; Wenjun Liao; Jiahui Zhou; Jianyi Zheng; Yueheng Wu; Dongfeng Li; Zhanyi Lin (Cell and Tissue Research, 2017)